STRATEGI MEMBANGUN KEMAMPUAN CRITICAL THINKING PADA GENERASI DIGITAL - Alwan, Muhammad (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract The ability to think critically is a must-have ability in the digital generation era, more specifically in the world of education. Because it is clear that the most important goal in today's modern education system is how to create a generation that has the capability in terms of critical thinking. Because this ability is a strong foundation in building the nation's civilization in the midst of increasing unstoppable digitalization. So to be able to build and develop these abilities, strategies are needed that can be manifested in the learning process in order to instill critical thinking skills in the digital generation. The method used in this research is literature study by collecting and reviewing library data which is then linked to research to obtain answers to problems. The results of the study show that there are many strategies that can be used to build critical thinking skills in children, especially the alpha generation or digital generation, namely (1) Problem Based Learning (PBL) strategies, (2) Learning with the help of technology, (3) Mobile Learning (M -Learning), (4) IMPROVE Method. These four methods are effective strategies in building students' critical thinking skills in welcoming the current digital era.